Was Jesus God? - Swinburne, Richard (Oxford University Press, 2008)
Richard Swinburne argues compellingly that if there is a God, then the main doctrines which the Christian Church teaches about God are very probably true. In particular, he shows that there is strong philosophical support for the belief that Jesus, while remaining God, acquired a human nature and lived on earth for thirty years as a human being. - ;The orderliness of the universe and the existence of human beings already provides some reason for believing that there is a God - as argued in Richard Swinburne's earlier book Is There a God? Swinburne now claims that it is probable that the main.